2020
DOI: 10.1016/j.ebiom.2019.11.023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fecal microbiota transplantation on IBS related quality of life and fatigue in moderate to severe non-constipated irritable bowel: Secondary endpoints of a double blind, randomized, placebo-controlled trial

Abstract: Background: Severity in irritable bowel syndrome (IBS) is associated to impaired quality of life and fatigue. Fecal microbiota transplantation (FMT) induces significant relief in gastro-intestinal related complaints. The objective was to evaluate the effect of FMT on the secondary endpoints: IBS-related quality of life and fatigue in patients with non-constipated IBS. Method: In this double-blind randomized placebo-controlled, parallel-group, single-center study, we enrolled patients with non-constipated IBS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 29 publications
3
34
0
2
Order By: Relevance
“…Huang et al and Johnsen et al assessed quality of life using the IBS-QOL scale. Scores on this questionnaire followed a similar pattern as the assessments above, with a significant improvement being observed during the first 3 to 6 months and returning to baseline after 6 to12 months [45,49]. Johnsen et al also found a similar effect on fatigue, with improvement up to 6 months after FMT and a waning effect from 6 to 12 months [49].…”
Section: Clinical Studiessupporting
confidence: 58%
“…Huang et al and Johnsen et al assessed quality of life using the IBS-QOL scale. Scores on this questionnaire followed a similar pattern as the assessments above, with a significant improvement being observed during the first 3 to 6 months and returning to baseline after 6 to12 months [45,49]. Johnsen et al also found a similar effect on fatigue, with improvement up to 6 months after FMT and a waning effect from 6 to 12 months [49].…”
Section: Clinical Studiessupporting
confidence: 58%
“…Treatment strategies targeting enteric microbiota, including antibiotics, pre-/pro-/symbiotics, a low-FODMAP (fermentable oligo-, di-, mono-saccharides, and polyols) diet, and fecal microbiota transplantation (FMT), have been found to be effective in certain populations [ 45 , 57 ]. Particularly, FMT appears to be one of the most powerful modalities to reverse dysbiosis and potentially induces long-lasting remission of IBS [ 58 , 59 ]. Recent study demonstrated that utilizing a well-defined donor with a normal dysbiosis index and favorable specific microbial signature is important for successful FMT in IBS patients [ 60 ].…”
Section: Role Of Intestinal Resident Microbiota In Ibs Pathologymentioning
confidence: 99%
“…The current evidence base for the effect of FMT in psychiatric disorders (predominantly anxiety and depression) has been previously summarised. 97 The overwhelming majority of in-human studies have enrolled patients with concurrent IBS [98][99][100][101][102] or are limited to case reports, [103][104][105] with only one study 98 involving a control group and blinding, making it difficult to draw firm conclusions at present. Improvements were seen in depression, anxiety, quality-of-life and fatigue scores, although the effect may only be transient.…”
Section: Anxiety and Depressionmentioning
confidence: 99%